MERGER DALAM HUBUNGANNYA DENGAN PERSAINGAN USAHA TIDAK SEHAT - Rihi, Megawati; Sudantra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013, 2013)
In essence, the conduct of business activities is to make profits and income in order to make ends meet. On the basis of subsistence is what drives a lot of people run a similar business activities or activities of different businesses. The state that is the actual cause or childbirth competition among businesses. The existence of more intense competition in the business world today, where big companies trying to find ways to improve its efficiency and wherever possible improve its performance. One way out is taken by either merge two or more companies.
Keywords: business, competition, efficiency, merger